LRG-BEASTS III: ground-based transmission spectrum of the gas giant orbiting the cool dwarf WASP-80. Issue 1 (31st October 2017) - Kirk, J.; Wheatley, P. J.; Louden, T.; Skillen, I.; King, G. W.; McCormac, J.; Irwin, P. G. J.
Abstract: We have performed ground-based transmission spectroscopy of the hot Jupiter orbiting the cool dwarf WASP-80 using the ACAM instrument on the William Herschel Telescope (WHT) as part of the Low-Resolution Ground-Based Exoplanet Atmosphere Survey using Transmission Spectroscopy programme. This is the third paper of a ground-based transmission spectroscopy survey of hot Jupiters using low-resolution grism spectrographs. We observed two transits of the planet and have constructed transmission spectra spanning a wavelength range of 4640–8840 Å. Our transmission spectrum is inconsistent with a previously claimed detection of potassium in WASP-80b's atmosphere, and is instead most consistent with a haze. We also do not see evidence for sodium absorption at a resolution of 100 Å.